The long shadow of the past : political economy of regional inequality in Colombia (2017)
We study the nature of regional inequality in Colombia over the past 200 years. The main empirical fact is that regional inequality has been highly persistent despite the large changes that have taken place and the modernization of the society. We show that regional inequality is highly correlated with significant within-country differences in economic and political institutions, which are themselves highly persistent over the same period. We propose a tentative political economy theory of why the spatial distribution of institutions and economic outcomes has been so persistent over time.